Tale of a robot: Humanoid robot assisted sign language tutoring - Köse, Hatice; Yorganci, Rabia (IEEE, 2011)
There is an on-going study which aims to assist in teaching Sign Language (SL) to hearing impaired children by means of non-verbal communication and imitation based interaction games between a humanoid robot and the child. In this study, the robot will be able to express a word in SL among a set of chosen words using hand movements, body and face gestures. Having comprehended the word, the child will give relevant feedback to the robot. In the current study, we propose an interactive story telling game between a NAO H25 humanoid robot and preschool children based on Turkish Sign Language (TSL). Since most of the children do not know how to read and write, and they are not familiar with sign language, we prepared a short story including specially selected words which is performed by the robot verbally and with sign language as well. The children are expected to give feedback to the robot with matching colour flashcards when it implements a word in sign language. The robotic event covered 106 preschool children. The aim is to evaluate the children's sign language learning ability from a robot, and comparison of these results with the results of video based studies.